2023
DOI: 10.3390/toxics11100809
|View full text |Cite
|
Sign up to set email alerts
|

Lead, Cadmium, and Arsenic in Raw Cow’s Milk in a Central Andean Area and Risks for the Peruvian Populations

Jorge Castro-Bedriñana,
Doris Chirinos-Peinado,
Elva Ríos-Ríos
et al.

Abstract: Milk and its derivatives are basic foods in Peru, especially for children. The Junín region, in the central Andes, is one of the leading dairy basins. However, the safety of milk is affected by mining–metallurgical activities, wastewater dumping, organic residues, and inappropriate use of organophosphate fertilizers in agriculture whose contaminants reach the food chain, putting human health at risk. The purpose of this study was to evaluate the bioaccumulation of lead (Pb), cadmium (Cd), and arsenic (As) in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…In these five studies, As levels are in the safe range and were not reported beyond the local standard limits of the studied countries and EU and FAO/WHO standards. Although the number studies related to measuring As in pasteurized and sterilized milk across the world was so limited; several studies evaluated As concentration in raw cow’s milk which report higher values than ours from Córdoba, Argentina with mean concentration between 0.0003 and 0.0105 mg/kg [ 8 ]; in Iran, in the range of 0.015 to 0.026 mg/kg [ 89 ], in Alabria, Italy, reporting an average As content of 0.038 mg/kg of raw milk, in Slovakia, with mean concentration of As < 0.03 mg/kg [ 8 , 10 ]. All these low concentrations of As in raw cow’s milk and pasteurized and sterilized milk are indicative that As use in the transformation of dairy products is safe for consumer and it does not pose health risks for human consumption.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In these five studies, As levels are in the safe range and were not reported beyond the local standard limits of the studied countries and EU and FAO/WHO standards. Although the number studies related to measuring As in pasteurized and sterilized milk across the world was so limited; several studies evaluated As concentration in raw cow’s milk which report higher values than ours from Córdoba, Argentina with mean concentration between 0.0003 and 0.0105 mg/kg [ 8 ]; in Iran, in the range of 0.015 to 0.026 mg/kg [ 89 ], in Alabria, Italy, reporting an average As content of 0.038 mg/kg of raw milk, in Slovakia, with mean concentration of As < 0.03 mg/kg [ 8 , 10 ]. All these low concentrations of As in raw cow’s milk and pasteurized and sterilized milk are indicative that As use in the transformation of dairy products is safe for consumer and it does not pose health risks for human consumption.…”
Section: Resultsmentioning
confidence: 99%
“…It was also evidenced that Cd generally comes from phosphate fertilizers that contain up to 53.2 mg/kg of Cd [ 9 ]. Besides, equipment used in the production and packaging process is the likely other source of contamination [ 8 , 10 ]. The contamination of containers and equipment used in milking and pasteurization processes and environmental contamination were accounted to be among the factors affecting the elevated Cd concentration in the collected milk samples in their study [ 8 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the central Peruvian Andes, La Oroya, one of the most polluted cities on the planet, has been the center of polymetallic metallurgical complexes for over 100 years, although there are few environmental impact studies and little attention paid to the risk of bioaccumulation in milk products from the surrounding areas [13,[34][35][36], especially in local populations, with little epidemiological and scientific evidence on the state of contamination of the soil-pasture-milk system and risk due to milk consumption. Specifically, the middle basin of the Mantaro River has an agricultural vocation and is the major supplier of milk and dairy products to the great city of Lima, from which processed products go to the entire country.…”
Section: Introductionmentioning
confidence: 99%